RESPONS PERTUMBUHAN TANAMAN SAWI PAKCOY (Brassica chinensis L.) TERHADAP PEMBERIAN AIR KELAPA TUA (Cocos nucifera). - Lia Setyawati; Marmaini Marmaini; Yunita Panca Putri (Indobiosains, 2020)
Pakcoy (Brassica chenensis L.) is a type of vegetable that belongs to the Brassicaceae family and is a short-lived plant. This research was conducted in April-May 2019. This study used a Completely Randomized Design consisting of 6 treatments and 4 replications. The purpose of this study was to determine the effect of the administration of old coconut water on the growth of pakcoy mustard plants and to find out at what dosage of coconut water can give the best results on mustard cabbage plants. The results showed that in plant height the lowest value was obtained in the treatment of P0 4.0 cm and the highest value in the treatment of P5 with a value of 4.71 cm. In the number of leaves obtained the lowest value in the P0 4.25 treatment strands and the highest value in the P5 treatment 4.62 strands. In the wet weight, the lowest value was obtained in the treatment of P0 0.15 grams and the highest value in the treatment of P5 0.18 grams. At the dry weight obtained the lowest value at P0 0.0625 gram treatment and the highest value at P5 0.0085 gram treatment.